Neuroscience and War: Human Enhancement, Soldier Rehabilitation, and the Ethical Limits of Dual-use Frameworks. (January 2017) - Howell, Alison
Recent breakthroughs in neuroscience have led to increasing concern about its uses in warfare. This article challenges the primacy of dual-use frameworks for posing ethical questions concerning the role of neuroscience in national security. It brings together three fields – critical war studies, bio-ethics, and the history of medicine – to argue that such frameworks too starkly divide 'good' and 'bad' military uses of neurotechnology, thus focusing on the degradation of human capacities without sufficiently accounting for human enhancement and soldier rehabilitation. It illustrates this through the emergence of diagnoses of Traumatic Brain Injury and Polytrauma in the context of post-9/11 counterinsurgency wars. The article proposes an alternative approach, highlighting the historical co-production and homology of modern war and medicine so as to grapple with how war shapes neuroscience, but also how neuroscience shapes war. The article suggests new routes for thinking through the connections between war, society, science, and technology, proposing that we cease analysis that assumes any fundamental separation between military and civilian life.